The National Centre for the Coordination of Territorial Ethics Committees for Clinical Trials of Medicines and Medical Devices for Human Use (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
The article outlines the structure, functions, and activities of Italy’s National Centre for the Coordination of Territorial Ethics Committees (CCNCE), established to oversee ethical evaluations of clinical trials. It details the legislative framework, operational mandates, and coordination with regional ethics committees (CETs), emphasizing the CCNCE’s role in harmonizing procedures, monitoring performance, and supporting ethical standards. The article also discusses challenges in governance, regulatory fragmentation, and the need for institutional collaboration to ensure effective clinical research oversight.
Keywords: ethics committees; human experimentation; Italy; legislation; research